The effectiveness of long Pulsed Nd:YAG Laser alone for treatment of keloids and hypertrophic scars versus its combination with bleomycin. (18th October 2021) - Ramadan, Heba; Saber, Mahmoud; Salah, Manal; Samy, Nevien
Abstract: Background and objectives: Pathological scars are benign hyper‐proliferative growths of dermal collagen that causes severe psychological and physical problems. This study was performed to assess and compare safety and clinical efficiency of combined pulsed Nd‐YAG laser and intralesional bleomycin versus pulsed Nd‐YAG laser alone to treat the hypertrophic scars and keloids. Patients and methods: Randomly, 40 patients with hypertrophic scars or keloids were divided into two groups A and B. Group A were handled by pulsed Nd:YAG laser and intralesional bleomycin while group B were handled by pulsed Nd:YAG laser only. Response was assessed subjectively by clinical imaging and modified Vancouver Scar Scale (mVSS). While for objective evaluation, skin biopsies were taken from volunteer patients before and after treatment, and were examined by Hematoxylin and eosin staining (H&E) and Masson trichrome staining. Results: Our study demonstrated almost complete improvement in 4 (20%) patients, partial improvement in 16 (80%) patients and 0 patient with no improvement in group A. Furthermore, in group B, we demonstrated almost complete improvement in 2 (10%) patients, partial in 14 (70%) patients and no improvement in 4 (20%) patients. Modified Vancouver Scar Scale reduced from 10.15 to 3.5 in group A and from 11.05 to 4.95 in group B. Elastica Masson‐Goldner staining and Hematoxylin and eosin staining showed that treatment in both groups structurally changed tissue collagen. Conclusion: Long‐pulsed Nd‐YAG laser combined with intralesional bleomycin could be a promising way for treatment of keloids or hypertrophic scars.